Dr. Christine Vogt William, Dr. Epifania Amoo-Adare and Ann-Marie Ellmann on knowledge-making - Vogt-William, Christine; Amoo-Adare, Epifania; Ellmann, Ann-Marie (Cluster Conversations, 2025)
In this episode of the Cluster Conversations, host Dr. Christine Vogt-William sits down with the Cluster's artist fellows Dr. Epifania Amoo-Adare and Ann-Marie Ellmann for a thought-provoking exchange on knowledge-making, creative research practices, and navigating the spaces between disciplines. Together, they explore how intellectual curiosity, personal experience, and collaborative inquiry shape their work within the Cluster – and beyond. Tune in for an inspiring conversation that blends reflection, insight, and a touch of scholarly playfulness.